Modeling, Optimization and Design Method of Metal Manufacturing Processes - Zhang, Guoqing; Zhao, Zejia; YIP, Wai Sze (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Metal manufacturing is a fundamental and indispensable technology in the processing of raw metals into desired products, which significantly promotes the development of industry and society overall. This book presents original research and a state of the art review of contemporary metal manufacturing processes, especially in the modeling, optimization, and design of the manufacturing processes. This book covers topics such as machine learning algorithms in manufacturing metal products, the fabrication and optimization of mechanical properties of metals, and numerical simulations and experiments in the machining of metals. The book presents some essential theories and successful manufacturing techniques for the low-cost and highly efficient production of metals.